(3ZGjI GdCJbGf aj CYeGd GdfTGH hGdUhdLGfs - (3GdWeTs
(3ChdgG (B:s
(3cJGH ai Yde GdaQhSjI GdMeO ddg Pi GdYXeI hGdLdGd GdeJYGdi Yf GdbOQI hGdUaGJ hGdCeKGd s
(3BNQgG (B:s
(3hRGaQI GdQeM (B: (3hSWg hSGadJg ahb ehVY RMI hLg GdSfGf GdPi jONd ajg WQa GdQeM hgh ef GdQeM GdKYdH hGddg CYde hgh Gdehab s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(32 / 3 (3b(B) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs